2021
DOI: 10.3389/fcimb.2021.656984
|View full text |Cite
|
Sign up to set email alerts
|

Subinhibitory Concentrations of Biogenic Silver Nanoparticles Affect Motility and Biofilm Formation in Pseudomonas aeruginosa

Abstract: Biogenic silver nanoparticles (bio-AgNPs) are increasingly recognized as an antibiofilm and antivirulence strategy against P. aeruginosa, a bacterium that causes chronic infections in immunocompromised and cystic fibrosis patients. This study aimed to investigate the effects of subinhibitory concentrations of bio-AgNPs on motility and biofilm formation in P. aeruginosa. Bio-AgNPs were synthesized via reduction of ionic silver catalyzed by cell-free culture filtrate from Fusarium oxysporum. A total of 17 P. aer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 49 publications
4
26
0
1
Order By: Relevance
“…Thus, we speculate that the three AgNPs can better achieve their antibacterial effects by inhibiting the swimming motility of bacteria. Our study is similar to Saeki et al [ 55 ], who reported that AgNPs can weaken the swimming diameter of Pseudomonas aeruginosa.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Thus, we speculate that the three AgNPs can better achieve their antibacterial effects by inhibiting the swimming motility of bacteria. Our study is similar to Saeki et al [ 55 ], who reported that AgNPs can weaken the swimming diameter of Pseudomonas aeruginosa.…”
Section: Resultssupporting
confidence: 92%
“…Previous studies showed that bacterial swimming is directly related to bacterial growth, biofilm formation, and pathogenesis [ 55 , 56 ]. In this study, the AgNPs synthesized by three plants showed a strong inhibitory effect on bacterial swimming ( Figure 5 b).…”
Section: Resultsmentioning
confidence: 99%
“…The study uses a cross-sectional design, with microorganisms that were isolated between 1 Janurary 2019 and 1 Janurary 2020, originating from various types of clinical specimens, being randomly selected to be included in our experiments. During the study, P. aeruginosa ATCC 27853 (MDR isolate, weak biofilm producer) and P. aeruginosa PAE 170022 (susceptible isolate, strong biofilm producer) were used as control strains, obtained from the American Type Culture Collection (Manassas, VI, USA) [ 24 ]. Stock cultures were stored at −80 °C in a cryopreservation medium (700 µL trypticase soy broth + 300 µL 50% glycerol) until use.…”
Section: Methodsmentioning
confidence: 99%
“…Data demonstrated that Er and Met I at 2 and 5 mg/L promoted biofilm formation, which is characterized by an increased number biofilm-dwelling cells and a reduced ROS level in comparison to the control samples. It is well known that some antimicrobials at sub-inhibitory concentrations can function as signalling molecules and promote biofilm formation while altering bacterial virulence, quorum sensing, gene expression and gene transfer [ 35 , 36 , 37 ]. Furthermore, the antioxidant N -acetylcysteine promoted biofilm growth in S. aureus ATCC25923 and Pseudomonas aeruginosa PAO1 by increasing expression of some biofilm-associated genes and enhanced extracellular polymers production [ 13 ].…”
Section: Discussionmentioning
confidence: 99%